1983
DOI: 10.1016/s0022-5347(17)52599-9
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Patients Started on Clean Intermittent Self-Catheterization Therapy 10 Years Ago

Abstract: We evaluated 60 patients placed on a clean intermittent catheterization program more than 10 years ago to determine their outcome. To date 27 patients still are performing self-catheterization, 18 have discontinued the procedure and 15 have been lost to followup. No patient has had deterioration in renal function. Prior incontinence was alleviated completely in 10 of the 27 patients still on the program and 10 of the 18 patients no longer on catheterization have returned to normal voiding. Clean intermittent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…This technique has been successful in a large number of adults and children on follow-up of more than 20 years. 7,8 Indeed, it is reported that clean ISC is more suitable than indwelling catheterization in patients who require long-term bladder drainage as a means of minimizing the histological changes that occur in the bladder mucosa that may predispose and lead to malignant transformation. 9,10 There are 7 reported cases in the published literature of SCC of the bladder due to a variety of reasons in patients using clean ISC (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been successful in a large number of adults and children on follow-up of more than 20 years. 7,8 Indeed, it is reported that clean ISC is more suitable than indwelling catheterization in patients who require long-term bladder drainage as a means of minimizing the histological changes that occur in the bladder mucosa that may predispose and lead to malignant transformation. 9,10 There are 7 reported cases in the published literature of SCC of the bladder due to a variety of reasons in patients using clean ISC (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Prevalences of complications vary in literature 9,10 but remain very acceptable also in the long term. The study presented here was performed to evaluate the use of the prelubricated catheter Urocath gel 1 in male patients who had used conventional catheters for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 shows that there were no differences in the mean age, the mean duration of postonset, the mean duration of CIC use and the mean time of each catheter usage between those with and without febrile UTI. For long-term management, besides proper daily frequency and technique of CIC/CISC, patients' compliance such as ability to properly perform CISC, mental capability and selfdiscipline, 11 it may be safer that one uses the silicone catheter for a shorter period of time; however, no exact time recommendation can be given so far.…”
Section: Discussionmentioning
confidence: 99%